Infrastructure and trade costs on ASEAN-5: land, sea and air - Ramli, Mohd Khairul Rafiz; Ismail, Normaz Wana (Faculty of Economics and Management, Universiti Putra Malaysia, 2012)
Trade costs may have significant impact on bilateral trade and can be caused by several factors, such as distance and infrastructural inefficiency. This study examines the determinants of trade costs and the role of physical infrastructure in ASEAN-5 member countries namely Malaysia, Indonesia, Philippines, Singapore and Thailand. Examining panel data from the period 1980 to 2009, regressions based on the standard panel data model show that land infrastructure, sea infrastructure, ICT and utilities, and port efficiency are statistically significant variables and have significant impacts on trade costs in this region.